Effect of Viral Double-Stranded RNA on Protein Synthesis in Intact Cells - Cordell-Stewart, B. (1973)
The addition of purified, noninfectious, double-stranded RNA of bovine enterovirus, a picornavirus, to intact cells in culture results in a rapid cessation of cellular polypeptide synthesis. This inhibition is specific for host cell protein synthesis since the translation of picornavirus-specific proteins is not affected by the double-stranded viral RNA.